Progression from early to advanced stage of immune‐related cholangitis. Issue 10 (15th August 2022) - Hagiwara, Satoru; Yoshida, Takeshi; Nishida, Naoshi; Ida, Hiroshi; Ueshima, Kazuomi; Minami, Yasunori; Takita, Masahiro; Aoki, Tomoko; Morita, Masahiro; Cishina, Hirokazu; Komeda, Yoriaki; Yoshida, Akihiro; et al.
Abstract: Aim: We report a rare case of immune‐related cholangitis in which the natural course could be demonstrated. Case Presentation: Eight courses of pembrolizumab maintenance therapy were given as first‐line treatment for squamous cell lung cancer; however, the patient was subsequently hospitalized due to a rapid increase in hepatobiliary enzymes. On endoscopic ultrasound, the common bile duct was dilated to 11 mm, and the wall, throughout its length from the papilla, was thickened. Endoscopic retrograde cholangiopancreatography showed no obvious stenosis in the lower bile duct; however, a parapapillary diverticulum was found, and papillary incision and bile duct plastic stent insertion were carried out. However, the liver disorder did not improve and overt jaundice appeared subsequently; therefore, an immune‐related cholangitis was suspected, and prednisolone (PSL) 35 mg/day was introduced from day 59 of admission. Following PSL initiation, a decrease in serum bilirubin level was observed; however, significant decrease was not observed in alkaline phosphatase. Given the history of recurrent infectious cholangitis, magnetic resonance cholangiopancreatography was carried out on day 70 of admission. The intrahepatic bile duct showed stenosis and dilated findings, which was considered to be a factor for repeated infectious cholangitis. Conclusion: No previous case reports have described the changes and progression in bile duct images in immune‐related adverse events. Therefore, this case is noteworthy for considering the progression of immune‐related cholangitis.